New concepts for spatial development in Germany - Lutter, Horst (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Spatial development concepts represent a desirable state of the spatial structure in the future. They are based on the analysis and evaluation of the state achieved so far and are once in a while adapted to the changing social and economic framework conditions. They are an important coordinating instrument in spatial planning. On the Federal spatial planning level, the Federation and the Länder are to jointly develop “concepts for the regional development of the national territory” in line with § 18 of the Federal Regional Planning Act. Following a large discussion process, the German Standing Conference of Ministers responsible for Spatial Planning (Ministerkonferenz für Raumordnung MKRO) decided on 30 June 2006 to launch new concepts and action strategies for spatial development in Germany. They cover current topics of spatial planning policy, i.e. growth and innovation, services for the public, protection of resources and development of cultural landscapes.